Unexpected excessive apixaban exposure: case report of a patient with polymorphisms of multiple apixaban elimination pathways - Huppertz, Andrea; Grond-Ginsbach, Caspar; Dumschat, Chris; Foerster, Kathrin; Burhenne, Jürgen; Weiß, Johanna; Czock, David; Purrucker, Jan; Rizos, Timolaos; Haefeli, Walter E. (BMC pharmacology & toxicology, 2019)
Apixaban effectively lowers the risk of ischemic stroke and systemic embolism in patients with non-valvular atrial fibrillation. Systemic exposure to a given apixaban dose depends on multiple clearance pathways. Though routine quantification of direct oral anticoagulants (DOACs) in neurological emergency situations has not been widely established, suspected associations of DOAC peak concentrations with bleeding events and DOAC trough concentrations with efficacy and safety suggest that such information might support clinical decision making.